TBX3 and ASIP genotypes reveal discrepancies in officially recorded coat colors of Hucul horses - M. Mackowski; L. Wodas; S.A. Brooks; J. Cieslak (Animal, 2019)
Although only a few specific pigmentation types are allowed within the Hucul horse registry, accurate determination of particular coat colors can be uncertain due to the presence of variation in color shades and segregation of multiple dun dilution variants. Herein, we genotyped the previously identified polymorphisms within two coat color loci TBX3 (T-box 3) and ASIP (Agouti Signaling Protein) in 462 Hucul individuals and compared the genotype predicted phenotypes with observed pigmentation types provided in the Polish Horse Breeders Association database. We identified disagreement between the predicted and recorded coat color in 157 horses (34%). The most common error was misclassification of horses with the nd1/nd1 and nd1/nd2 genotypes, what may be related with the occurrence of some ‘intermediate’ dilution phenotypes in such individuals. We have also proven that the frequency of the dominant dun dilution allele (D) (0.30) is higher than previously predicted by available studbooks. The D allele(s) is easily ‘hidden’ in various phenotypic groups including dark bay and black, therefore we hypothesized that the dun dilution effect itself is not as strongly epistatic in the Hucul horse as described in other horse breeds. This may be the result of an additional genetic modifier suppressing D allele phenotypic effect.